VD_FINDINFO AI 43/09 - 136/2010 vom 6. April 2010 - VD Tribunal cantonal (2010)
RÉVISION DE LA RENTE, DEGRÉ DE L'INVALIDITÉ, FORCE PROBANTE | 1 LAI, 17 LAI, 28 al. 1 LAI, 4 al. 1 LAI, 16 LPGA, 17 LPGA, 56 LPGA, 7 LPGA, 8 LPGA, 117 al. 1 LPA-VD, 55 al. 1 LPA-VD, 91 LPA-VD, 93 al. 1 let. a LPA-VD, 94 al. 1 let. a LPA-VD